Downtrends in Offside Offenses Among ‘The Big Five’ European Football Leagues - Zhao, Yangqing (Frontiers in Psychology, 2021)
This study examined the evolution of offside offenses and pass performance across a 10-season period in the top 5 European soccer leagues. Match performance observations (n = 18 259) were analysed for emergent trends. Two-way ANOVA analyses revealed significant league and seasonal differences among the five leagues (medium effect size). The total offside offenses committed during a match experienced a clear decline during the 10 seasons. In contrast, moderate increases were evident for all passing differential variables. Offside offenses per match were higher in the German Bundesliga and Spanish La Liga than in the English Premier League and France Ligue 1. However, the English Premier League had the greatest value in the touch differential, pass differential, successful pass differential and key pass differential among all leagues. It is important to note that the number of offside offenses fell after the implementation of VAR.